Extreme regulator structure grounding of automated process productivity of electric discharge machining - Савеленко, Григорий Владимирович; Ермолаев, Юрий Алексеевич (Technology audit and production reserves, 2014)
The use of process productivity extreme regulator of dimensional arc processing in engineering is discussed in the article and some results of our research in this area are given. The main aim of the investigation is finding the output patterns of its functions on stabilized and unstabilized process segments of dimensional arc processing on proposed implementation of the regulator. The use of modern control systems of electric discharge machining process allows processing the materials with higher energy efficiency and less resource consumption. A variant of solving the problem of finding the productivity extremum of dimensional arc processing based on stochastic and different frequency disturbances is proposed in the article. The presented implementation of extreme regulator allows automating the process of finding and maintaining the feed rate of electrode-tool, at which the maximum process efficiency is obtained. The research results can be used by designers, engaged in the field of process automation of electrode-tool advance during electric discharge machining of metals.